Incomplete Plasmodium falciparum growth inhibition following piperaquine treatment translates into increased parasite viability in the in vitro parasite reduction ratio assay - Walz, Annabelle; Sax, Sibylle; Scheurer, Christian; Tamasi, Balint; Mäser, Pascal; Wittlin, Sergio (Frontiers in Cellular and Infection Microbiology, 2024)
Antimalarial resistance to the first-line partner drug piperaquine (PPQ) threatens the effectiveness of artemisinin-based combination therapy. In vitro piperaquine resistance is characterized by incomplete growth inhibition, i.e. increased parasite growth at higher drug concentrations. However, the 50% inhibitory concentrations (IC50) remain relatively stable across parasite lines. Measuring parasite viability of a drug-resistant Cambodian Plasmodium falciparum isolate in a parasite reduction ratio (PRR) assay helped to better understand the resistance phenotype towards PPQ. In this parasite isolate, incomplete growth inhibition translated to only a 2.5-fold increase in IC50 but a dramatic decrease of parasite killing in the PRR assay. Hence, this pilot study reveals the potential of in vitro parasite viability assays as an important, additional tool when it comes to guiding decision-making in preclinical drug development and post approval. To the best of our knowledge, this is the first time that a compound was tested against a drug-resistant parasite in the in vitro PRR assay.